"Honest Toil": Labor, the Body, and Citizenship in the Knights of Labor, 1880–1890. Issue 1 (1st January 2016) - Keohane, Jennifer
Abstract : In this essay, I analyze anti-Chinese rhetoric produced by the Knights of Labor to explore how labor functions as a performance of citizenship. I argue that Knights deployed citizenship as a embodiable topos, using the physicality of labor as a channel to claim inclusion in the national polity despite their marginalized class status.